Constructed rain garden systems for stormwater quality control under tropical climates - Sidek L.M.; Muha N.E.; Noor N.A.M.; Basri H. (Institute of Physics Publishing, 2023)
Malaysia has taken an integrated approach to manage storm water that is increasingly becoming a problem in big cities. Rain gardens are recommended as green technology for a new storm water management in Malaysia. The approach is applied in urban planning and design that integrates the total water cycle management into the development process areas. Rain gardens have been effective in reducing peak discharge and consistently reduce the number of storm water pollutants. This paper will examine some of guidelines, laboratory studies and field monitoring that shows great potential and benefit of rain garden. The preliminary results for rain garden performance were reported in this paper. The findings from this research will open avenues for researchers to advance the knowledge in rain garden systems to achieve the sustainable development in Malaysia. Published under licence by IOP Publishing Ltd.